ANNOTATED TRANSLATION OF CURRICULUM TERMINOLOGY IN INDONESIAN ACADEMIC TRANSCRIPT - Maya Rizki Fauzia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Transcript is an official document that comprises a student’s academic record. Besides all courses taken, grades received and cumulative GPA, it also consists of specific terms or expressions in the target language. Translating official document requires special attention since the process deals with transferring meaning and finding appropriate terms in Indonesian. This study is based on annotated translation of academic transcript from Indonesian to English. Its objectives are to identify issues the researcher encountered in the process of translating the document from the Source Language (SL) to the Target Language (TL), and provide solutions to the translation problems. The units of analysis were 11 annotations of problems which consisted of 3 words and 8 phrases related to curriculum. The result showed that translation problems occurred due to lacking understanding on meaning of curriculum-related terminology. Semantic and functional translation methods were the strategies employed to obtain a suitable equivalent for the problems. Another strategy was to consult to official documents providing more detailed information on the terminology.